The prevalence of headache disorders in Postural Tachycardia Syndrome: A systematic review and meta-analysis of the literature. (October 2022) - Ray, Jason C; Pham, Xiuxian; Foster, Emma; Cheema, Sanjay; Corcoran, Susan J; Matharu, Manjit S; Hutton, Elspeth J
Background: Headache is a common presentation of postural tachycardia syndrome, yet robust prevalence data is lacking. Objectives: To undertake a systematic review and meta-analysis to estimate the prevalence of headache disorders in postural tachycardia syndrome, and to explore the potential shared pathophysiological mechanisms that underpin these conditions as well as treatment options. Methods: Three databases were searched for publications evaluating prevalence of migraine (primary outcome) and general and orthostatic headache (secondary outcomes) in patients with postural tachycardia syndrome. Two independent reviewers selected studies and extracted data. A random-effects meta-analysis calculated the pooled prevalence of migraine in postural tachycardia syndrome. A narrative literature review explored the pathophysiology and treatment options for concurrent headache disorders and postural tachycardia syndrome. Results: Twenty-three articles met inclusion criteria. Estimated pooled prevalence of migraine in postural tachycardia syndrome was 36.8% (95% CI 2.9–70.7%). Various shared pathophysiological pathways for these conditions, as well as proposed treatment strategies, were identified. Limitations : Heterogeneity of study design, populations, and methodology for identifying headache disorders and postural tachycardia syndrome limited the generalisability of results. Conclusions: Migraine is a commonly reported comorbidity in POTS, however the true prevalence cannot be determined from the current literature. Further studies are required to assess this comorbidity and investigate the underlying mechanisms, as well as identify effective treatment strategies.